Non-prescription pharmacy syringes sales to people who inject drugs (PWID) in Khartoum, Sudan: policy, practice, and perceptions. (4th May 2022) - Siddig, Ahmed; Elhassan, Mohamed; Ali, Mazin M.; Farah, Abduraheem; Elkhalifa, Mohammed; Elawad, Emeirii H.; Hassan, Israa; Haboura, Omnia; Digna, Mutaz F.; Mohamedalhadi Alamin Alkhalifamohamed, Hussam
ABSTRACT: Background: People who inject drugs (PWID) are at high risk of contracting blood-borne infections. Many developed countries started a needle exchange program to provide PWID with sterile syringes. In Sudan, healthcare professionals are exposed to legal liability if they cooperate with people who use drugs; therefore, the accessibility to sterile syringes without prescription depends heavily on pharmacists' knowledge and attitude toward PWID. Objectives: Assessing policy, practice, and perceptions of pharmacists toward selling sterile syringes to PWID in Khartoum, Sudan. Methods: A self-administered questionnaire was given to 157 pharmacists (57 male, 100 female). Results: Out of 157 participating pharmacists, 86.6% reported selling syringes without a medical prescription, 53.5% inquired about the reason for buying syringes, and 87.9% refused to sell the syringes to a PWID. 43.3% of participating pharmacists were uncertain about the presence of law to regulate selling syringes without prescriptions. Although 47.7% of the participants agreed that selling empty syringes without a medical prescription to PWID will reduce harm, 68.5% will not sell them to PWID without a medical prescription even if it is encouraged by law due to their religious or moral beliefs. Conclusion: Pharmacists are the main providers of clean syringes for PWID in Khartoum, Sudan. With the majority of them reporting refusal to provide syringes to PWID, this may put PWID at higher risk of contracting blood-borne infections due syringe sharing. This is a challenge to overcome in planning for effective harm reduction programs in Khartoum.